USING EXPERIMENTAL PLANNING TO OPTIMIZE THE HYDROLYSIS OF SUGAR CANE BAGASSE INTO FERMENTABLE SUGARS FOR BIOETHANOL PRODUCTION BY FUNGAL ENZYME MIXTURE - Giap, Vu Dinh; Chi, Do Huu; Hai, Pham Hong; Chinh, Tang Thi; Nghi, Do Huu (Vietnam Journal of Science and Technology, 2017)
In this study, the unpretreated sugar cane bagasse was milled to a particle size of 0.5 – 1 mm and be used as material for bioconversion into fermentable sugars by using an enzyme cocktail acted synergistically. Experimental planning was used to optimize the enzyme conversion through assessment and analysis of individual parameter. As the result, the optimal condition for enzymatic conversion of sugar cane bagasse into reducing sugar product are at pH = 5, 400C, and 48 h incubation in rate of enzyme (Cell/Xyl, AltFAE, XpoAE) and substrate (bagasse meal) is 3.1. From the above application, the mathematical model is found to describe equation of the bioconversion of bagasse into reducing sugars: = 206.946 + 29.954x1 + 5.501x2 + 7.323x3 + 2.288x2x3 – 7.011; and using flexible algorithm of nonlinear planning to identify optimal conditions of enzyme mixture of conversion into reducing sugars that the reaction reached max = 251.86 mg per gram bagasse with x1 = 1.215, x2 = 1.215, x3 = 1.215 or Cell/Xyl = 1 ml (100U), AltFAE = 0.5 ml (7.56U), XpoAE = 0.4 ml (10.8U) on the test range. Experimental verification has the same result in constant conditons and reached total reducing sugars of 260.2 mg per gram substrate.